Perancangan Pintu Otomatis Berbasis Arduino Menggunakan Sensor Pir - Salamun Haris; Firman Santoso; Farihin Lazim (Elkom: Jurnal Elektronika dan Komputer, 2024)
Traditional doors usually consist of a housing or padlock and a flip key to open it. Usually found on office or mall doors, doors can be made more practical. The door will open automatically if there is physical energy (stimulus) that moves it. For example, when someone wants to enter the room, the door will automatically open. Doors like this are designed using automatic control using embedded system equipment. This automatic door system can be designed using automatic control combined with PIR sensors and servo motors. In terms of input equipment, a PIR (Passive Infrared Receiver) sensor is used which will detect humans approaching the door. This PIR sensor will send a signal to the Arduino process unit which contains a microcontroller chip. This microcontroller will send the processed data to the servo motor, so that it can open or close the door automatically.